2014
DOI: 10.5888/pcd11.130330
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes and Associated Obesity in Pennsylvania Adults, 1995–2010

Abstract: IntroductionThis study examined trends in the prevalence and sociodemographic distributions of diabetes and the associations of diabetes with obesity over time in adult Pennsylvanians from 1995 through 2010.MethodsWe used Behavioral Risk Factor Surveillance Survey data collected from 1995 through 2010. Diabetes prevalence was assessed by self-report of physician diagnosis. Obesity was assessed by body mass index computed from self-report of height and weight. State-level data for diabetes and associated obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…This situation seems to be worse in developing countries, where the healthcare system often fails to meet demand [ 6 ]. Studies have concluded that a Western dietary pattern, sedentary lifestyle, and genetic factors play a central role in diabetes development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…This situation seems to be worse in developing countries, where the healthcare system often fails to meet demand [ 6 ]. Studies have concluded that a Western dietary pattern, sedentary lifestyle, and genetic factors play a central role in diabetes development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in a study that used various biochemical measurements for diagnosis, a higher prevalence of diabetes in men was found [6]. Another study concluded that the western dietary pattern, physical inactivity and genetic factors play a fundamental role in the development of diabetes [13]. Furthermore, it was reported that the incidences of diabetes increase with age, obesity, physical inactivity and unhealthy diet [14] [15].…”
Section: Discussionmentioning
confidence: 99%
“…In a southeastern Wisconsin population, excess weight gain during childhood was a risk factor for early manifestation of Type 1 diabetes mellitus (Evertsen et al, 2009). In Pennsylvania, researchers found the burden of obesity and diabetes is extensive and growing (Garcia-Dominic et al, 2014). The reason of the expansion of diabetes prevalence due to high obesity prevalence in Northern US is still not well understood from previous studies, so it is necessary to conduct further work in counties vulnerable to diabetes, especially in West North Central and East North Central regions.…”
Section: Articlementioning
confidence: 99%